2010
DOI: 10.1097/cji.0b013e3181d32e74
|View full text |Cite
|
Sign up to set email alerts
|

Cancer and Inflammation: Promise for Biologic Therapy

Abstract: Cancers often arise as the end stage of inflammation in adults, but not in children. As such there is a complex interplay between host immune cells during neoplastic development, with both an ability to promote cancer as well as limit or eliminate it, most often complicit with the host. In humans, defining inflammation and the presence of inflammatory cells within or surrounding the tumor is a critical aspect of modern pathology. Groups defining staging for neoplasms are strongly encouraged to assess and incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
193
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 293 publications
(204 citation statements)
references
References 136 publications
4
193
0
7
Order By: Relevance
“…The severity, timing, and local character of any particular inflammatory response, initiated by tissue damage, depends on the cause, location and site of the area affected, and host's condition [8]. Inflammatory oncotaxis, a term used to describe tumor growth at a site of inflammation, is occasionally seen in persons with known or occult cancer and who have local trauma [9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…The severity, timing, and local character of any particular inflammatory response, initiated by tissue damage, depends on the cause, location and site of the area affected, and host's condition [8]. Inflammatory oncotaxis, a term used to describe tumor growth at a site of inflammation, is occasionally seen in persons with known or occult cancer and who have local trauma [9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation occurs in various types of tumor, and serves a crucial function in tumor development and distant metastasis (7)(8)(9)(10). Previous studies have indicated that inflammation is associated with the formation of the tumor microenvironment by inflammatory mediators, including vasoactive amines and cytokines (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to a clinical therapy, but there are problems: pyruvate is relatively unstable in aqueous solution and the hunt for a possible alternative here currently led, for example, to the development of ethyl pyruvate, which is a simple aliphatic ester derived from pyruvate, but as well contributed to the invention of stable aqueous solutions containing sodium pyruvate using H + (pH 3.0 -6.0) or additional Na + (20 mM) [22] [70]- [72]. And in fact, the first results seem to be promising: treatment with pyruvate or ethyl pyruvate has shown to improve survival and/or ameliorate organ dysfunction in a wide variety of pre-clinical models or clinical trials of acute illnesses such as severe sepsis, acute pancreatitis, respiratory distress syndromes, stroke, cancer or in patients undergoing cardiac surgery [18] [35] [70]- [79]. Furthermore, the therapy using pyruvate or pyruvate-related compounds was also shown to be safe, but, nevertheless, in most studies it failed to improve outcome.…”
Section: Resultsmentioning
confidence: 99%
“…catalysed by the enzymes pyrroline-5-carboxylate synthase, ornithine aminotransferase, ornithine carbamyltransferase, or carbamylphosphate synthase) or the synthesis of •NO which is required for neutrophil activation [33] [34]. And indeed, a growing consensus exists regarding a so-called "pyruvate-glutamate-ketoglutarate-arginine-ornithine-system", which especially in leukocytes, appears to hold a key role as an "intracellular turntable for amino nitrogen metabolisation" [32] [35]. The advantages to the cell seems obvious: the possibility of a rapid transition into other essential cell substrates (i.e.…”
Section: Pyruvate Induced Effects: Is There An Impact By Adding a Glumentioning
confidence: 99%